2004
DOI: 10.1038/labinvest.3700191
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transforming growth factor β decreases pancreatic fibrosis and protects the pancreas against chronic injury in mice

Abstract: Transforming growth factor-b (TGF-b) is an important cytokine in the fibrogenesis in many organs, including the pancreas. Using an adenoviral vector expressing the entire extracellular domain of type II human TGF-b receptor (AdTb-ExR), we investigated whether inhibition of TGF-b action is effective against persistent pancreatic fibrosis, and whether it exerts a beneficial effect on the pancreas in the process of chronic injury. To induce chronic pancreatic injury and pancreatic fibrosis, mice were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 42 publications
3
51
1
Order By: Relevance
“…Curcumin blocked TGF-b 0 s profibrotic actions through down-regulation of TGF-b receptor type II expression and inhibition of cjun activity [Gaedeke et al, 2004]. Because TGF-b plays a key role in the development of pancreatic fibrosis [Nagashio et al, 2004], it is interesting to see whether curcumin affects the TGF-b signaling cascade in PSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin blocked TGF-b 0 s profibrotic actions through down-regulation of TGF-b receptor type II expression and inhibition of cjun activity [Gaedeke et al, 2004]. Because TGF-b plays a key role in the development of pancreatic fibrosis [Nagashio et al, 2004], it is interesting to see whether curcumin affects the TGF-b signaling cascade in PSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Because type I collagen is the predominant matrix in the desmoplastic reaction (4,5), and because genetic studies have shown that MT1-MMP is a primary regulator of interstitial collagenolysis (16), our data suggest that inhibition of TGF-h1 signaling would also help to block tumor progression in vivo. Importantly, TGF-h1 has also been shown to promote a desmoplastic reaction in vivo following orthotopic transplantation of TGF-h1-transfected pancreatic cancer cells in an experimental model of human pancreatic carcinoma (46), whereas conditional loss of TGF-h1 signaling within the pancreas significantly ameliorated chemical-induced pancreatic fibrosis (47,48). Based on our data and on recent reports showing that the desmoplastic reaction is detrimental to the host (7,35), modulation of TGF-h1 signaling using small-molecule inhibitors, a number of which are currently under development (49), could be a potential approach for the treatment of this highly lethal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among pancreatic stromal cells, PSCs attracted great attention due to their central role in pancreatic fibrosis, and multiple cytokines and growth factors have been reported to activate PSCs. For example, platelet-derived growth factor (PDGF), TGF-b, angiotensin II and tumor necrosis factor-a are well-known activators of PSCs [38][39][40][41]. These ligands activate downstream signaling pathways that promote cell proliferation, survival, migration and the ECM production of PSCs.…”
Section: Detailed Mechanism Of Psc Activation In Pancreatic Cancermentioning
confidence: 99%